1997
DOI: 10.1029/97jb01425
|View full text |Cite
|
Sign up to set email alerts
|

Subduction‐related structures in the North Iberian Margin

Abstract: Abstract. The oblique convergence of Eurasia and Iberia since the Early Cretaceous, caused the formation of the Pyrenean intracontinental collisional orogen in the east, and progressed to continent-ocean collision with subduction of the Bay of Biscay oceanic crust beneath the North Iberian Margin in the west. Two deep multichannel seismic profiles (IAM-12 and ESCIN-4), integrated with gravity modeling and other geological and geophysical data, provide the crustalscale architecture of this margin and its tecton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 30 publications
7
112
0
Order By: Relevance
“…Ambiguous evidence of Iberia subduction exists in the area. In fact, while both gravimetric data (Alvarez-Marrón et al, 1997) and seismic velocity modelling S. Tavani: Plate kinematics in the Cantabrian domain 269 (Fernández-Viejo et al, 1998) Fig. 2) shows a repetition of the lower crust-mantle boundary (Ayarza et al, 1998) matching a north-directed subduction of Iberia.…”
Section: The Crustal-scale Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…Ambiguous evidence of Iberia subduction exists in the area. In fact, while both gravimetric data (Alvarez-Marrón et al, 1997) and seismic velocity modelling S. Tavani: Plate kinematics in the Cantabrian domain 269 (Fernández-Viejo et al, 1998) Fig. 2) shows a repetition of the lower crust-mantle boundary (Ayarza et al, 1998) matching a north-directed subduction of Iberia.…”
Section: The Crustal-scale Architecturementioning
confidence: 99%
“…Elevation map with main faults of the Iberia-Eurasia collisional margin and orogenic domains marked and crustal-scale cross sections. P1: geological cross section across the Pyrenees (after Muñoz, 1992); P2: geological cross section across the Basque Pyrenees (after Pedreira et al, 2007); P3: geological cross section across the Cantabrian Mountains (modified from Gallastegui, 2000); P4: geological cross section across the western termination of the Cantabrian domain (modified from Alvarez-Marrón et al, 1997). P5: geological cross section along the Cantabrian shelf (modified from Ayarza et al, 1998).…”
Section: The Crustal-scale Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The ESCIN and MARCONI programs and other related projects were planned to study the deep crustal structure and evolution of the Cantabrian Mountains and continental margin from deep seismic reflection and refraction/wideangle data (Pérez-Estaún et al, 1994;Pulgar et al, 1995Álvarez-Marrón et al, 1996Álvarez-Marrón et al, , 1997Gallastegui et al, 1997;Ayarza et al, 1998;Fernández-Viejo et al, 1998, 2000Gallastegui, 2000;Gallastegui et al, 2002;Fernández-Viejo and Gallastegui, 2005;Fernández-Viejo et al, 2011. These studies showed that the deformation of the area due to the Alpine compression affected not only the shallow crustal levels but also the deeper ones.…”
Section: Introductionmentioning
confidence: 99%
“…From the Eocene onwards the subduction of oceanic crust in the Bay of Biscay beneath the Iberian continental margin led to the formation of an incipient subduction zone (Figure 9) (Sibuet and Le Pichon, 1971;Boillot et al, 1979;Grimaud et al, 1982;Roest and Srivastava, 1991;Alvarez-Marrón et al, 1997). The subduction continued until the Early Miocene (Boillot et al, 1979;Roest and Srivastava, 1991), and possibly into the Neogene , 1997.…”
Section: Discussionmentioning
confidence: 99%